Globalization of Services in Practice. (Analysis of Success on Polish Example in the Years 2003-2011) - Wyrwicz, Marek (Acta Agraria Debreceniensis, 2012)
The globalised world is looking for savings and actually finds it in Poland. Global economy is a system of connected vessels, functioning in close relations, with increasing role of Poland. The text demonstrates the developmental perspectives of outsourcing and offshoring in the largest Polish metropolies and the possibilities of the development of smaller cities.